Clinical and Imaging Characteristics on 3.0T mpMRI of Prostate Cancer - Huu Chung, Nguyen; Thanh Dung, Le; Dinh Minh, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Abstract: Objective: To describe the clinical and multiparametric MRI (mpMRI 3T) features in patients suspected of prostate cancer (PCa) with PI-RADS ≥ 3. Materials and Methods: A cross-sectional descriptive study was conducted on 139 patients who underwent mpMRI with PI-RADS ≥ 3 and had histopathological confirmation. Clinical and imaging characteristics including age, symptoms, total PSA, free PSA, PSA density, prostate volume, lesion location, T2-weighted imaging (T2W), apparent diffusion coefficient (ADC), and dynamic contrast enhancement (DCE) were compared between the PCa group (Gleason score ≥ 7) and the non-PCa group. Results: Among 139 patients, 66 (47.5%) were diagnosed with PCa. The main symptoms in both PCa and non-PCa groups were obstructive (83.3% vs. 93.2%) and irritative (53% vs. 50.7%) urinary symptoms. All five patients presenting with bone pain belonged to the PCa group (p = 0.017). Total PSA, free PSA, and PSA density were significantly higher in the PCa group (p < 0.001). Lesions involving both the peripheral zone (PZ) and transition zone (TZ) had a 10.5 times higher risk of PCa compared to lesions limited to the PZ (p < 0.001). PI‑RADS 5 lesions were associated with a 139-fold higher risk of PCa than PI‑RADS 3 lesions (p < 0.001). Markedly low ADC signal was a strong predictor of PCa with an odds ratio (OR) of 79.5 (95% CI: 26.47–240.84), sensitivity of 89.4%, and specificity of 90.4%. Conclusion: Bone pain and elevated PSA are strong clinical indicators of prostate cancer. On MRI, lesions involving both PZ and TZ, PI‑RADS 5 scores, and markedly reduced ADC signal are strong predictors of malignancy. Keywords: Prostate cancer, mpMRI, PI‑RADS, ADC, PSA.